Utilization of hog blood plasma as binder in skinless pork longganisa - Rucero, Marian Arlyn R.
The study was conducted to utilize blood plasma as binder in pork longanisa. It was divided into three phases. Phase I which dealt with the development of an optimum blood plasma incorporation level was divided into two subphases. In Phase Ia, binding capacities of samples containing varying levels of plasma binder (1.0%, 1.25%, 1.50% 1.75% and 2.00%) were measured. This was done to identify an "ideal range" by evaluating the effectivity of the binder at various levels. An "ideal range" of 1.50% to 2.0% was established. At these range sausages showed increasing binding capacities (measured as tensils strength). In Phase IB the "ideal range" was optimized through sensory evaluation test for cohesiveness. Longanisa containing 1.50%, 1.75% and 2.00% plasma binder showed no differences. Thus, the highest optimum level (2.00%) was chosen as the incorporation level. At this level, utilization of blood plasma was maximized. In Phase II of the study, the selected incorporation level was standardized through comparison with control samples. Control samples containing 0.3% phosphate binder were found to be superior in terms of flavor strength and binding capacity as compared to experimental samples. However, experimental samples were found to be comparable to control samples containing 1% cornstarch binder. Protein content analysis showed that sausages containing plasma binder had a relatively higher protein content compared to the two control samples. The standardization of formulation and process done in Phase III produced cooked skinless pork longanisa with the following attributes: reddish brown to pinkish red color, tender texture, ideal or characteristic longanisa flavor, and an odor that is just right. The general acceptability of the final product was given an average score of seven (7), "like moderately".